1985
DOI: 10.1159/000145941
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Starvation on the Ultrastructure of the Mouse Parathyroid Gland

Abstract: Ultrastructural changes of the parathyroid glands of starved mice were examined. The parathyroid glands of the starved mice showed a decrease in the volume of Golgi complexes and storage granules and an increase in the volume of lipid droplets, and contained more heterogeneously dense bodies and multivesicular bodies compared with that of the control mice. In addition, the volume of mitochondria, cisternae of granular endoplasmic reticulum and secretory granules and the number of prosecretory granules appeared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
(31 reference statements)
2
9
0
Order By: Relevance
“…These findings on the Golgi apparatus and cisternae of the rough endoplasmic reticulum in the in vivo and in vitro study are fairly consistent with the observations which indicate a decrease in functional activity of the parathyroid gland (Isono et aL, 1980(Isono et aL, , 1982(Isono et aL, , 1983(Isono et aL, , 1985 Therefore, it is suggested that Mg acts as a suppressive factor for the synthesis of PTH in the short term, and directly affects the chief cell of the hamster parathyroid gland. …”
Section: Stereological Analysis Of the Parathyroid Glandsupporting
confidence: 89%
“…These findings on the Golgi apparatus and cisternae of the rough endoplasmic reticulum in the in vivo and in vitro study are fairly consistent with the observations which indicate a decrease in functional activity of the parathyroid gland (Isono et aL, 1980(Isono et aL, , 1982(Isono et aL, , 1983(Isono et aL, , 1985 Therefore, it is suggested that Mg acts as a suppressive factor for the synthesis of PTH in the short term, and directly affects the chief cell of the hamster parathyroid gland. …”
Section: Stereological Analysis Of the Parathyroid Glandsupporting
confidence: 89%
“…We think that the large secretory granules are storage granules, as reported earlier Isono et aL, , 1981Isono et aL, , 1982Isono et aL, , 1985Isono et aL, , 1990Setoguti et al, 1981;Shoumura et al, 1988aShoumura et al, -d, 1989aShoumura et al, , b, 1990.…”
Section: Discussionsupporting
confidence: 71%
“…Recent morphological reports have suggested that in the chief cells of the parathyroid glands in the starved mice (Isono et al, 1985) and golden hamsters ) the number of lipid droplets were increased as compared to those of the control animals.…”
Section: Discussionmentioning
confidence: 96%
“…It has been described that the hypoactive chief cells showed an increase in lipid droplets (Isono et al, 1980(Isono et al, ,1982(Isono et al, ,1983Hayashi et al, 1981;Shoumura et al, 1988). Furthermore, it has been demonstrated that the chief cells of the parathyroid gland in the starved mice showed a decrease in the Golgi complexes and cisternae of the granular endoplasmic reticulum (Isono et at., 1985). Therefore, result of our study suggests that starvation affects functional activity in the water-clear cells as well as in the chief cells of the parathyroid glands in the adult and senile golden hamsters.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation